Agro-industrial residues in the control of gastrointestinal nematodes of small ruminants and fertilization of forages - Izabella Cabral Hassum; Henrique Antunes de Souza; Tânia Maria Leal; Rita de Kássia Oliveira Tavares; Raimundo Bezerra de Araujo Neto; Jenefer de Oliveira Nunes; José Alves Pereira Neto (Ciência Rural, 2023)
ABSTRACT: Verminosis in small ruminants can render rural activity impractical, which is still controlled through the administration of anthelmintics. The present study evaluated four agro-industrial residues as fertilizer in the control of GIN of small ruminants in the free-living stage. Crab shell, manipueira, biochar, and organomineral residues were used in pots (5.0 kg of soil) and cultivated with Massai grass (Megathyrsus maximum cv. Massai). Further, the pots were contaminated with feces from sheep carrying a natural multispecific infection by GIN. Next, the residues were applied individually to the soil, with 50 mL/pot for liquid and 50 g/pot for solid residues. Treatment with manipueira showed the lowest number of L3.kg MS-1 recovered from the grass (202.44), when compared with treatments using organomineral (823.89) and biochar (689.34). However, there was no statistically significant difference (P < 0.05) between the four treatments as compared to the control group. These agro-industrial residues can be used as organic fertilizers; however, these will not help in the control of GIN in sheep.